DETERMINAN PEMBIAYAAN MURABAHAH (Studi Kasus Pada PT. Bank Muamalat Indonesia, Tbk.) - Vaidian, Elok Vivin; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is aimed to examine the influence of third party funds, the influence of non performing financing, the influence of return on assets to the murabaha financing. The sample collection technique has been carried out by using purposive sampling. The sample is PT. Bank Muamalat Indonesia in 2007-2014 research periods. The data analysis technique has been performed by using multiple linear regressions. The result of the research indicates that third party funds has positive influence since the bank tends to distribute their funds as much as possible in order to gain maximum profit. Non Performing Financing has negative influence because the loans which return to the bank is less, it will make the funds which is available to be distributed decreased. Meanwhile, the Return on Assets has positive influence because when the profit rate that is gained by the bank is getting large, the management efforts to invest the profit with various activities which benefit the management is getting strive as well, particularly the distribution of financing. Keywords: third party funds, non performing financing, return on assets, murabaha financing.